Mesin Pendeteksi Uang Palsu Dengan Sensor LDR Berbasis Kecerdasan Buatan - Sri Maharani; Jhonson Efendi Hutagalung; Abdul Karim Syahputra (Building of Informatics, Technology and Science (BITS), 2022)
Money is a very important thing for human life in meeting the needs of life, as a medium of exchange in payment for the buying and selling process. The importance of money causes some people to try to have as much money as possible, even in a way that is against the law like make and circulate counterfeit money. Counterfeit money is counterfeit currency that is produced without legal authorization and permission from the state or government. The circulation and manufacture of counterfeit money is very detrimental to the economy of the country and the small community because it is difficult to distinguish counterfeit money by naked eye and tools to detect counterfeit money are not commonly used and existing tools do not detect paper money through the holographic bars contained in banknotes. The purpose of this study was to determine whether banknotes were included in the original or counterfeit category using LDR sensors, ultrasonic sensors, UV lamps, lasers, and UV sensors. Ultrasonic function to read the distance, if appropriate, it will automatically turn on the UV lamp which will be captured by the UV sensor, so that the holograms on the banknotes can be clearly seen and the laser is used to illuminate the bars on the money if the laser does not penetrate and the light will be received by the banknote. LDR sensor that adjusts to a predetermined value range, the results can be seen on the LCD screen and hear the sound from the speakers. It is hoped that the existence of this money detector can be used to help people avoid the circulation of counterfeit money and develop it further